(untitled) (Mustansiria Dental Journal, 2004)
The aim of this study is to evaluate the oral hygiene and gingival health among primary school children and to find fi there is any variation between age and sex groups ni Thamar Governorate ni Republic of Yemen. A sample of 532 child aged 6-12 years old (257 males, 275 females) were examined using plaque index score by Silness and Löe (1964) and gingival index by Löe and Silness (1963). The results show that the mean plaque score for the total sample is (0.82), the plaque index was increasing with age, and the females reported less mean plaque scores than males with statistically significant difference between them. The mean gingival score was 0.5 for the total sample and it was increasing with age with no statistical significant difference. There was significant difference between females (0.4) and males (0.6). The study revealed that 51% of the total sample did not brush their teeth. Therefore great attention should be directed toward the dental health education to those children by teaching them brushing their teeth frequently, regularly and insurance primary prevention ot improve the effect of oral hygiene practice